Murder uncorked - Day, Maddie (Day, Maddie. Cece Barton mystery., 2024)
"As the manager of Vino y Vida Wine Bar in Colinas, Cecelia "Cece" Barton's first Alexander Valley harvest is a whirlwind of activity. Her twin sister, Allie Halstead, who owns a nearby Victorian bed & breakfast, is accustomed to the hustle and bustle of peak tourist season. But Cece barely has a moment to enjoy her new home in between worrying about her estranged college-age daughter, juggling her responsibilities at the bar, and navigating the sticky politics of the local wine association. Just when it seems things can't grow any more intense, Colinas is rocked by a murder within the wine community... and Cece is identified as a possible suspect! With her reputation and her livelihood on the line--and the Sonoma County deputy sheriff breathing down her neck--Cece has no choice but to open up her own murder investigation. Tensions are already high in the valley, as a massive wildfire creeps toward Colinas, threatening homes, vineyards, and the vital tourist trade. And now, with a murderer on the loose, and Cece's sleuthing exposing the valley's bitterest old rivalries and secret new alliances, Colinas feels ready to pop! But with Allie's help, Cece is determined to catch the killer and clear her name before everything she's worked so hard for goes up in flames..."--